Transforming Growth Factor Beta Receptor 2 (TGFBR2) Promoter Region Polymorphisms May Be Involved in Mandibular Retrognathism. (15th June 2022) - Kirschneck, Margarita; Zbidat, Nermien; Paddenberg, Eva; Reis, Caio Luiz Bitencourt; Madalena, Isabela Ribeiro; Menezes-Oliveira, Maria Angélica Hueb de; Lepri, César Penazzo; Proff, Peter; Kirschneck, Christian; Küchler, Erika Calvano
Abstract : Skeletal malocclusions are common phenotypes in humans and have a strong influence on genetic factors. Transforming growth factor beta (TGF β ) controls numerous functions of the human body, including cell proliferation, differentiation, and migration. Thus, this study is aimed at evaluating whether genetic polymorphisms in TGFB1 and its receptor TGFBR2 are associated with mandibular retrognathism in German children and adolescents. Children and teenagers older than 8 years in the mixed or permanent dentition were included in this study. Patients with syndromes and facial trauma and patients with congenital alterations were excluded. Digital cephalometric tracings were performed using the anatomical landmarks point A, point B, sella (S), and nasion (N). Patients that have a retrognathic mandible (SNB < 78 °) were selected as case group, and the patients with an orthognathic mandible (SNB = 78 °– 82°) were selected as the control group. Genomic deoxyribonucleic acid (DNA) from saliva was used to evaluate four genetic polymorphisms in TGFB1 (rs1800469 and rs4803455) and TGBR2 (rs3087465 and rs764522) using real-time PCR. Chi-square or Fisher exact tests were used to compare gender, genotype, and allele distribution among groups. Genotype distribution was calculated in an additive and recessive model. Haplotype analysis was also performed. The established alpha of this study was 5%. A total of 146 patients (age ranging from 8 to 18 years) were included in this epidemiological genetic study. The genetic polymorphism rs3087465 in TGFBR2 was associated with mandibular retrognathism. Carrying the AA genotype in the rs3087465 polymorphism decreased the chance of having mandibular retrognathism (odds ratio = 0.25, confidence interval 95 % = 0.06 to 0.94, p = 0.045 ). None of the haplotypes was associated with mandibular retrognathism (p > 0.05 ). In conclusion, we found that the genetic polymorphism rs3087465 in the promoter region of the TGFBR2 was associated with mandibular retrognathism in Germans.